Cloaked in Courage.: Women´s Coats as Co-agents of Resistance: Transversal Realities in Central Europe, 1935–1953 - Križalkovičová, Zuzana (Dějiny – teorie – kritika, 2024)
This study investigates the role of women's coats as active participants in various resistance movements across Central Europe from 1935 to 1953, employing a posthumanist framework to reexamine issues of subjectivity. By integrating theories of material culture and new materialism, the research moves beyond traditional anthropocentric views to highlight the dynamic inter-actions between women and their coats within a resistance context. This approach demonstrates that the garments were not merely passive symbols of defiance but multifaceted tools that provided physical protection, facilitated the covert transmission of messages and materials and reinforced the wearers' resolve and solidarity. Through historical analyses, personal testimonies and cultural artifacts, this study demonstrates how coats functioned as co-agents in resistance activities, both shaping and being shaped by the social, cultural, and political landscapes of the time. The study underscores the importance of recognizing the agency of material objects in historical narratives, offering a nuanced understanding of women's resistance activities and the broader implications for posthumanist thinking on identity and subjectivity.